The prevalence of lymphogranuloma venereum infection in men who have sex with men: results of a multicentre case finding study. Issue 3 (15th February 2009) - Ward, H; Alexander, S; Carder, C; Dean, G; French, P; Ivens, D; Ling, C; Paul, J; Tong, W; White, J; Ison, C A
Abstract : Objective: To determine the prevalence of lymphogranuloma venereum (LGV) and non-LGV associated serovars of urethral and rectal Chlamydia trachomatis (CT) infection in men who have sex with men (MSM). Design: Multicentre cross-sectional survey. Setting: Four genitourinary medicine clinics in the United Kingdom from 2006–7. Subjects: 4825 urethral and 6778 rectal samples from consecutive MSM attending for sexual health screening. Methods: Urethral swabs or urine and rectal swabs were tested for CT using standard nucleic acid amplification tests. Chlamydia-positive specimens were sent to the reference laboratory for serovar determination. Main outcome: Positivity for both LGV and non-LGV associated CT serovars; proportion of cases that were symptomatic. Results: The positivity (with 95% confidence intervals) in rectal samples was 6.06% (5.51% to 6.66%) for non-LGV CT and 0.90% (0.69% to 1.16%) for LGV; for urethral samples 3.21% (2.74% to 3.76%) for non-LGV CT and 0.04% (0.01% to 0.16%) for LGV. The majority of LGV was symptomatic (95% of rectal, one of two urethral cases); non-LGV chlamydia was mostly symptomatic in the urethra (68%) but not in the rectum (16%). Conclusions: Chlamydial infections are common in MSM attending for sexual health screening, and the majority are non-LGV associated serovars. We did not identify a large reservoir of asymptomatic LGV in the rectum or urethra. Testing for chlamydia from the rectum and urethra should be included for MSM requesting a sexual health screen, but serovar-typing is not indicated in the absence of symptoms. We have yet to identify the source of most cases of LGV in the UK.